2000
DOI: 10.2307/177339
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Synchrony of Spruce Budworm Outbreaks in Eastern North America

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. We investigated the spatial synchrony of outbreaks of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 33 publications
(68 reference statements)
10
103
1
1
Order By: Relevance
“…Although our study and those reviewed by Ray and Hastings (1996) focused on very different ranges of spatial scales, both appear to confirm the effect of averaging over subpopulations, which was postulated by those authors to lower the detection of density dependence at larger spatial scales. Our recent work on spatial synchrony of spruce budworm defoliation (Williams and Liebhold 2000) adds strength to this argument. Across eastern North America, spatial synchrony of defoliation times series decreased with distance between the series.…”
Section: Discussionmentioning
confidence: 79%
“…Although our study and those reviewed by Ray and Hastings (1996) focused on very different ranges of spatial scales, both appear to confirm the effect of averaging over subpopulations, which was postulated by those authors to lower the detection of density dependence at larger spatial scales. Our recent work on spatial synchrony of spruce budworm defoliation (Williams and Liebhold 2000) adds strength to this argument. Across eastern North America, spatial synchrony of defoliation times series decreased with distance between the series.…”
Section: Discussionmentioning
confidence: 79%
“…Using spatio-temporal analyses of I. typographus populations, Økland and Bjørnstad (2003) found that large windfall events may be a major synchronizer of beetle outbreaks. This strong association with precipitation and wind is generally not as great for forest Lepidoptera, and they may be more heavily influenced by variation in temperature (Koenig et al 1994;Koenig and Knops 1998;Koenig et al 1999;Koenig and Knops 2000;Williams and Liebhold 2000). Temperature fluctuations tend to be synchronous over longer distances than precipitation (Koenig 2002) or large windfall events (Økland and Bjørnstad 2003), and this may partially explain why Lepidoptera species exhibit more extended synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…Although outbreak maps are good indicators of forest insect populations at high densities, the relationship between infestation level and actual population density is generally nonlinear, thresholded, and subject to considerable variation (Williams et al 1991;Liebhold et al 1993;Williams and Liebhold 2000), though the relationship for I. typographus appears to be linear (Lindelo¨w and Schroeder 2000). While there may remain some questions about whether the observed differences in synchrony reflect true differences in population densities or not, our results indicate that there are substantial differences in levels of spatial synchrony among different forest insect taxa.…”
Section: Discussionmentioning
confidence: 99%
“…covering hundreds of square kilometres, have most often been associated with species exhibiting cyclic population dynamics, including lepidoptera (e.g. Myers 1998;Williams and Liebhold 2000;Klemola et al 2006), game birds (e.g. Ranta et al 1995a;Cattadori et al 1999) and mammals (e.g.…”
Section: Introductionmentioning
confidence: 99%